Front Cover: Solid‐State Structure of a Bromo(difluoromethylenephosphonato)cuprate – a Key Intermediate for the Synthesis of α, α‐Difluoromethylenephosphonates (Eur. J. Inorg. Chem. 29/2017). Issue 29 (19th July 2017) - Alter, Christian; Neumann, Beate; Stammler, Hans‐Georg; Weber, Lothar; Hoge, Berthold
Abstract : The cover picture shows the most important feature of the present paper, the X‐ray structure of bromo(difluoromethylenephosphonato)cuprate. This compound is mentioned in various reports, and we were determined to isolate it and drag its structure into the spotlight. As this structure contains copper and zinc, two heavy metals, we are presenting this heavy metal ensemble on a stage. The structure is highlighted with spotlights and framed by the coupling reaction it catalyzes. A concert‐like atmosphere is created by the dark background and the audience. Details are discussed in the article by B. Hoge et al. on page 3489 ff (https://doi.org/10.1002/ejic.201700526 ). For more on the story behind the cover research, see the Cover Profile (https://doi.org/10.1002/ejic.201700817 ).